Structural Transformation in the Blue-Green Nexus: Maritime Trade, Conservation Areas, and Energy Intensity Patterns - Suparta, I. Wayan; Wahyudi, Heru; Aida, Neli; Nirmala, Tiara (International Journal of Energy Economics and Policy, 2025)
Improving energy efficiency is one of the key pillars in the transition to a low-carbon economy and sustainable development. However, amidst increasing urbanization, labor force growth, and renewable energy adoption, energy intensity in Emerging markets and developing economies (EMDEs) still shows a stagnant trend. This indicates the existence of non-sectoral structural dynamics that have not been fully identified in previous literature. This research is motivated by the urgent need to quantitatively examine how multidimensional transformation affects national energy efficiency in EMDEs countries. This study aims to analyze the influence of container port traffic (container trade volume), marine protected areas (% of territorial waters), urban population (% of total population), labor force participation rate (% of working-age population), and renewable energy consumption (% of total final energy consumption), on the energy intensity level of primary energy in EMDEs countries over the period 2017-2021. Based on previous theoretical studies and empirical trends, it is hypothesized that container port traffic, and marine protected areas, urbanization, and renewable energy consumption reduce energy intensity, while labor force participation tends to increase energy intensity if not accompanied by sectoral and technological reforms. The research methodology uses a panel data regression approach with the Fixed Effect Model. The analysis shows that partially, container port traffic, and marine protected areas, urban population, and renewable energy consumption have a negative and significant effect on energy intensity, while labor force participation rate shows a positive and significant effect. Simultaneously, the five variables have a significant effect on energy intensity. The coefficient of determination (R2) of 0.994898 indicates that 99.48% of the variation in energy intensity can be explained by the variation in the five independent variables. This finding confirms the importance of policy formulation that integrates demographic structural transformation, renewable energy transition, maritime trade infrastructure modernization, and marine environmental governance to sustainably reduce energy intensity in EMDEs countries.